Coexistence of Papillary Thyroid Carcinoma With Thyroid MALT Lymphoma in a Patient With Hashimoto's Thyroiditis: A Clinical Case Report. Issue 52 (December 2015) - Shen, Guohua; Ji, Ting; Hu, Shuang; Liu, Bin; Kuang, Anren
Abstract : Abstract: Papillary thyroid carcinoma (PTC) is the most common type of thyroid neoplasias; however, primary thyroid gland lymphoma (PTL) is uncommon and their simultaneous occurrence is very rare. Herein, we reported a 25-year-old female patient with Hashimoto's thyroiditis (HT), who developed a small goiter with a palpable 1.2-cm nodule in the right lobe. A fine-needle aspiration (FNA) biopsy revealed atypical follicular epithelial cells and lymphoid cells in a background of lymphocytic thyroiditis. A total thyroidectomy was performed. The pathology showed multicentric papillary thyroid carcinoma, concomitant thyroid mucosa-associated lymphoid tissue (MALT) lymphoma, and Hashimoto's thyroiditis. Postoperatively, he received chemotherapy and radioactive iodine ablation treatment. Nowadays the thyroglobulin of the patient is undetectable, without recurrences at 2 years of follow-up. It is concluded that the PTC and MALT lymphoma can exist concomitantly, especially in patients with HT. For the diagnostic workup and optional management of this rare coexistence, a multidisciplinary approach and close surveillance are needed.